2003
DOI: 10.1292/jvms.65.1047
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Coxiella burnetii Infections among Cats in Different Living Environments

Abstract: ABSTRACT. The seroprevalence of Coxiella burnetii infection among pet cats in Japan and Korea and stray cats in Japan was investigated by an indirect fluorescent antibody technique and PCR test. Forty-four (14.2%) of 310 pet cats in Japan were seropositive, as were 15 (41.7%) of 36 stray cats in Japan and 10 (8.6%) of 116 pet cats in Korea. The antibody positive rate in stray cats was significantly higher than that in pet cats, but there was no correlation between the rates in Japanese and Korean pet cats. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 13 publications
2
47
1
4
Order By: Relevance
“…There is no report of an urban Q fever outbreak in Japan. However, seroepidemiology of companion animals shows the presence of C. burnetii in urban residential areas of Japan; 60 of 589 (10%) and 95 of 632 (15%) dogs [6,16] and 16 of 100 (16%), 23 of 150 (15%) and 44 of 310 (14%) cats [8,14,16] were reported as seropositive. Also, the DNA of the bacteria was detected in 2 dogs [9] and 4 of 310 (0.3%) companion cats [8], and the bacteria was isolated from 9 of 29 (31%) companion cats [15].…”
mentioning
confidence: 99%
“…There is no report of an urban Q fever outbreak in Japan. However, seroepidemiology of companion animals shows the presence of C. burnetii in urban residential areas of Japan; 60 of 589 (10%) and 95 of 632 (15%) dogs [6,16] and 16 of 100 (16%), 23 of 150 (15%) and 44 of 310 (14%) cats [8,14,16] were reported as seropositive. Also, the DNA of the bacteria was detected in 2 dogs [9] and 4 of 310 (0.3%) companion cats [8], and the bacteria was isolated from 9 of 29 (31%) companion cats [15].…”
mentioning
confidence: 99%
“…In present study, breed, type of housing, type of food and presence of clinical signs showed no significant differences between positive and negative cases. Based on the literature, high prevalence of C. burnetii has been reported in the urine of dogs and human infection has been directly linked to the pet dogs (Komiya et al, 2003;Tozer et al, 2014). Therefore, no clinical signs of positive cases might have a decisive role in human infections.…”
Section: Discussionmentioning
confidence: 99%
“…Les chiens et les chats peuvent aussi être infectés par C. burnetii et être associés avec des infections humaines dans les régions rurales et urbaines . Ainsi, au Japon, les chats sont considérés comme l'un des plus importants réservoirs de C. burnetii (Komiya et al 2003). Il faudrait des investigations plus poussées pour vérifier la transmission inter-espèce et exclure la circulation indépen-dante de différentes souches spécifiques d'espèce comme cela a déjà été démontré chez les ruminants domestiques (Roest et al 2013b).…”
Section: Les Réservoirsunclassified